The Alternative Use Of Water Hyacinth and Reed As Attached Growth Of Microbial In Waste Water Treatment - Hery Purnobasuki; Nur Indradewi Oktavitri; Tri Nurhariyati; B. Saadah; Santini Ika Rafsanjani (Institut Teknologi Sepuluh Nopember, 2014)
Aquatic plants have ability to decrease of waste water contaminant. The Water Hyacinth (Eichornia crassipes) and Reed (Imperata cylindrical) are aquatic plants which have ability to reduce concentration of BOD, TSS, COD, Total Nitrate and Total Phosphate in wetland. The other side, it can be used for media support in anaerobic treatment. Because of their abilities, there is some possibilities that Water Hyacinth and Reed can be used as attached growth of microorganisms. The aims of this study was to investigate the potential of water hyacinth and reed as attached media of microbe growth. Part of the plants are used is the trunk part. A slices of trunk is 1 cm. The analysis were conducted for 14 days with ratio 60% waste water and 40% air of reactor. Results of this study for water hyacinth that TSS decrease up to 71%. COD and Total Phosphate decrease 60%, Total Nitrate decrease 85%. While, for reed, TSS decrease up to 41%. COD decrease 56%, Total Phosphate decrease 41%. Total Nitrate decrease 10%. In conclusion, both of them had a potential as attached media of microbe growth. But, Water Hyacinth was better as media support than reed.